DETERMINANT OF THE INTENTION TO USE CHATGPT AMONG STUDENTS OF FACULTY OF SCIENCE AND TECHNOLOGY - M Ridwan; Hani Maulida Hasibuan; Amru Yasir (Universitas Dharmawangsa, 2024)
This study explored the effect of perceived usefulness, perceived ease of use, and, lifestyle compatibility, to use ChatGPT among Students of Science and Technology Faculty of UINSU Medan using the unified theory of acceptance and use of technology (UTAUT). This quantitative study adopted a cross-sectional research design to gather data from 130 respondents using a Google Form. The collected data were analyzed using partial least square structural equation modelling (PLS-SEM). As a result, perceived usefulness, perceived ease of use, and lifestyle compatibility, displayed a significant positive effect on intentions to use ChatGPT. The study outcomes serve to inform managers of faculty and university to devise effective strategies that capture students’ intention to use and experience of using ChatGPT in the learning process..